Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Pelaku Usaha Mikro Kecil dan Menengah di Kota Kupang - Eugenius Krisensio Lobang Tang; Yohanes Demu; Siprianus G. Tefa (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aims to analyze the factors that affect the level of compliance of Micro, Small and Medium Enterprises (MSMEs) taxpayers in Kupang City. The type of research used is case study research with a quantitative approach. Data was collected through a questionnaire distributed to 189 respondents who were selected using the purposive sampling technique. Data analysis was carried out using binary logistic regression with the help of SPSS version 25 software. The results of this study show that taxpayer awareness, supervision and enforcement of tax laws, benefits felt by taxpayers, as well as tax support and incentives significantly affect taxpayer compliance; Meanwhile, understanding of tax regulations and ease of tax administration does not affect taxpayer compliance. However, overall, the six independent variables have a simultaneous effect on taxpayer compliance as a dependent variable. This finding is expected to be the basis for local governments and related institutions in formulating policies that support increasing the compliance of MSME taxpayers in Kupang City.